Misappropriation of assets: A decepticon of leakages in Malaysian public sector - Haron, Rosmawati; Mohamed, Nafsiah; Paino, Halil (2015)
Decepticon, true to its name, may transform into various disguise.The villain take many forms from a flashy luxurious cars to even military vehicles. Similar to Decepticon, the episodes of misappropriation of assets in government sector runs from small misuse of stationeries to misuse of official vehicles for personal interest. It is indeed a leakage of expenditure to the government because the authority has spent unnecessary costs to cater this type of crime.Many has regarded asset misappropriation as harmless.Though the incidences might not be significant, yet, if it is left untreated, the authority will spend more money than it should. Hence, the objectives of this study is to find the empirical evidence on awareness against fraud deterrence among Malaysian public servants. As propositions, this study resolved on the inspiration that resilience against frauds can be developed through trainings, effective enforcement and control.Barrier such employees’ character should be considered as deterrence for fraud awareness. Based on Rules no.4.(2)(c) of Peraturan-Peraturan Pegawai Awam (Kelakuan dan Tatatertib) 1993 (Pindaan 2002), this research employed semi-structural interview method to capture details and descriptive data so that this study is able to get the comprehensive understanding on the missing link between government inspiration and practice.4 public servants ranging from 1 to 20 years of service have been selected for our preliminary studies to validate our research propositions.In effect, despite of that the policy is massively available in the government’s portal, the respondent claimed that they were not familiar with Rules no.4.(2)(c) and their decisions on the do’s and don’ts are entirely dependable on their faith and internal strength.Mentality of public servants is identified as key barrier towards awareness of fraud deterrence.There were few studies on fraud deterrence in Malaysian public sector.This study focus on the same scenario, yet supplemented with a study on fraud awareness amongst the government servant.